HOTS-Speed Test Integrated Quantum Learning Model: Can Improve Mathematical Concept Mastery? - I Wayan Eka Mahendra (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2022)
This study aims to improve mathematics learning outcomes (MLO) through the Quantum learning model integrated HOTS-Speed test. This research is classroom action research (CAR). The subjects of this study were 40 students of class XI Jasa Boga 1 SMK Pariwisata Harapan Denpasar for the academic year 2020/2021. This research was conducted in 2 cycles, where at the end of each cycle students were given an MLO test. The data collected in the next cycle was analyzed descriptively to calculate the average MLO score with a minimum success indicator of 75% minimum completeness criteria. From the analysis results obtained, the average score in the first cycle did not meet the indicators of success, while in the second cycle it had fulfilled so that the research was stopped in cycle 2. The conclusion of this study was that there was an increase in HBM through the application of the HOTS-Speed test integrated Quantum learning model. The increase in MLO occurs through changes in learning that researchers do. The HOTS-Speed test integrated Quantum learning model was able to improve students' MLO. Thus, the Quantum learning model assisted HOTS-Speed test is one solution in improving MLO.